The clinical, functional, and radiological features of hand osteoarthritis: TLAR-osteoarthritis multi-center cohort study - DURUÖZ, MEHMET TUNCAY (My University, 2022)
Objectives: This study aims to evaluate the clinical, functional, and radiological features of hand osteoarthritis (OA) and to examine their relationships in different geographic samples of the Turkish population. Patients and methods: Between April 2017 and January 2019, a total of 520 patients (49 males, 471 females; mean age: 63.6 +/- 9.8 years) with hand OA were included in the study from 26 centers across Turkey by the Turkish League Against Rheumatism (TLAR). The demographic characteristics, grip strengths with Jamar dynamometer, duration of hand pain (month), the severity of hand pain (Visual Analog Scale [VAS]), and morning stiffness were evaluated. The functional disability was evaluated with Duruoz Hand Index (DHI). The Kellgren-Lawrence (KL) OA scoring system was used to assess the radiological stage of hand OA. Results: The DHI had significant correlations with VAS-pain (r=0.367, p0.05). The differences between the groups of radiological hand OA grades in terms of age (p=0.007), VAS-pain (p0.05 for all). Conclusion: In our population, the patients with hand OA had pain, functional disability, and weak grip strength. The functional impairment was significantly correlated with the severity of the pain, and the functional status was worse in high radiological hand OA grades.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Health Sciences; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Romatoloji; Rheumatology